Emotional Labor Levels Of Nurse Academicians - (:unkn) unknown (ELSEVIER SCIENCE BV, 2015)
This study aimed to identify the emotional labor levels of nurse academicians and was conducted with 152 nurse academicians working at nursing departments of public and private universities in Istanbul. According to the results, the mean score of the scale was 3.01 +/- 0.51 in total, 1.68 +/- 0.69 in superficial acting dimension, 2.86 +/- 1.24 in deep acting dimension, and 4.49 +/- 0.55 in expression of naturally-felt emotions dimension. Nurse academicians working at public universities for at least 6 years evaluated the emotional labor score in total and in deep acting dimension higher than the others (p < 0.05). In conclusion, they performed mid-level emotional labor in general. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Emotional labor; nurse; academicians; university; WORK; PERCEPTIONS; STRATEGIES; IDENTITY; RULES